Novel thermostable lipase produced by a thermo-halophilic bacterium that catalyses hydrolytic and transesterification reactions - Febriani; Naiwatul Aura; Pati Kemala; Nurdin Saidi; Teuku M. Iqbalsyah (Heliyon, 2020)
Lipase belongs to the class of hydrolytic enzymes that are widely used in the biotechnology industries. The goal of this research was to purify and characterize lipase produced from a thermo-halophilic bacterium, namely Pria Laot Sabang 80 (PLS 80). Purification was performed using ammonium sulphate fractionation, followed by gel filtration chromatography using Sepharose Cl-6B. After purification, the enzyme had a specific activity of 326.6 U/mg with a purity of 6.02 higher than the crude extract; with a molecular weight of around 50 kDa. The optimum activity was observed at 70 °C and pH 9. The activity increased in the presence of 10 mM Mn2+, K+ and Ca2+ ions, while Hg2+ only slightly increased the enzyme activity. In contrast, the activity decreased in 10 mM Mg2+, Zn2+, Co2+, EDTA, and PMSF. The enzyme showed good hydrolytic activity on long fatty acids substrates (p-nitrophenyl palmitate) with a value of 35.5 U/mL. It was also able to catalyze a transesterification reaction. GC-MS result showed that the biodiesel consisted of methyl octanoate (5.3%), methyl caprate (12.4%), methyl laurate (34.1%), methyl myristate (10.7%), methyl palmitate (3.9%), and methyl stearate (1.2%) when using coconut oil as the substrate. The results suggested that the lipase from PLS 80 had unique attributes that could be useful in various industrial applications.